(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Custodial death is very sensitive issue at the core of human rights commission’s vocation and soul of every constitution. These cases of profound medico-legal importance require thorough objective assessment by forensic pathologists in panel autopsies amid allegations of police torture, lack of proper and timely medical care, vested monetary state compensations and media involvement with risks of communal disharmony. Custodial death cases presenting to nodal tertiary care teaching institution for post-mortem examination under duly constituted panel autopsy boards during last ten years were analysed for scientific delineation of various causal and associated factors. Study centre located in heart of Indian capital provided rare conglomeration of diverse cases bound to generate immense scientific interest. Authors discuss wide array of medico-legal aspects with related factors and circumstances in custodial deaths whilst causations regarding deaths were found to be natural in majority of cases.